Influence of using different translucent composite resins for customizing fiber post on the bond strength of self-adhesive cement to root dentin - Lima, Reinaldo Oliveira [UNESP]; Barros, Antonia Patricia Oliveira [UNESP]; de Melo Alencar, Cristiane; de Figueiredo Pereira, Kamila [UNESP]; Galvani, Lucas David [UNESP]; Vaz, Luís Geraldo [UNESP]; de CAMPOS, Edson Alves [UNESP]; Kuga, Milton Carlos [UNESP] (Japanese Society for Dental Materials and Devices, 2024)
This study evaluated the influence of different translucent resins (Z350 and Opallis) for customizing fiber posts and light-curing the cementation system using different LED equipment (V, Valo or R, Radii-Cal) on the bond strength and adhesive failure pattern at 24 h and 6 months. Eighty roots were prepared and divided into 4 groups (n=20): ZV (Z350 resin and LED Valo), ZR (Z350 resin and LED Radii-Cal), OV (Opallis resin and LED Valo), OR (Opallis resin and LED Radii-Cal). After post space preparation, the fiber post was customized and cemented with self-adhesive cement and light-curing using V or R LED equipment. Bond strength values were submitted to 2-way ANOVA test. ZV and ZR showed higher bond strength values than the other groups at 6 months of evaluation (p<0.05). The Z350 resin has a favorable influence on the bond strength of self-adhesive cement to root dentin, regardless of the LED polymerization equipment used.
Keywords: Adhesive; Bond strength; Cementation; Failure; Fiber post